Composite sandwich impact response: experimental and numerical analysis (Fracture and Structural Integrity, 2018)
The use of composite materials allows to have a great flexibility in terms of mechanical and physical characteristics. One of the most used composite structure in naval field, is the sandwich, which is composed by a stacking sequence of different plies. The designer, in preliminary phase, must handle a great quantity of degree of freedom (types of materials, orientation of the fibres, position along the stack, thickness, etc.) in order to reach the best compromise between mechanical behaviour, environmental impacts and production costs. Finite Element analysis represents a useful tool in order to optimize all these parameters and to estimate the outcome of experimental tests at design stage. The main goal of this work is to develop and to validate a FE model for the simulation of a particular family of composites, widely used in naval field and, in particular, in High Speed Crafts and powerboats. The first part of the paper concerns the experimental tests on two different types of sandwich specimens. Two families of tests were conducted: four-point bending tests and impact drop tests. The second part of the paper focuses on the validation of a FE model for both experimental setups.
Keywords: Finite Element; Lightweight composites; Sandwich composites; Offshore powerboats; Impact tests